High-density genetic linkage map construction and cane cold hardiness QTL mapping for Vitis based on restriction site-associated DNA sequencing - Su, Kai (BMC Genomics, 2020)
BACKGROUND: Cold hardiness is an important agronomic trait and can significantly affect grape production and quality. Until now, there are no reports focusing on cold hardiness quantitative trait loci (QTL) mapping. In this study, grapevine interspecific hybridisation was carried out with the maternal parent ‘Cabernet sauvignon’ and paternal parent ‘Zuoyouhong’. A total of 181 hybrid offspring and their parents were used as samples for restriction-site associated DNA sequencing (RAD). Grapevine cane phloem and xylem cold hardiness of the experimental material was detected using the low-temperature exotherm method in 2016, 2017 and 2018. QTL mapping was then conducted based on the integrated map. RESULTS: We constructed a high-density genetic linkage map with 16,076, 11,643, and 25,917 single-nucleotide polymorphism (SNP) markers anchored in the maternal, paternal, and integrated maps, respectively. The average genetic distances of adjacent markers in the maps were 0.65 cM, 0.77 cM, and 0.41 cM, respectively. Colinearity analysis was conducted by comparison with the grape reference genome and showed good performance. Six QTLs were identified based on the phenotypic data of 3 years and they were mapped on linkage group (LG) 2, LG3, and LG15. Based on QTL results, candidate genes which may be involved in grapevine cold hardiness were selected. CONCLUSIONS: High-density linkage maps can facilitate grapevine fine QTL mapping, genome comparison, and sequence assembly. The cold hardiness QTL mapping and candidate gene discovery performed in this study provide an important reference for molecular-assisted selection in grapevine cold hardiness breeding.